Hemitrygon yemenensis sp. nov., a new species of stingray (Myliobatoidea: Dasyatidae) from the northwestern Indian Ocean - Moore, Alec B. M.; Last, Peter R.; Naylor, Gavin J.p. (Zootaxa, 2020)
A new stingray, Hemitrygon yemenensis sp. nov., is described from old preserved material collected on the Arabian Sea coast of eastern Yemen. Consistent with other members of the genus, H. yemenensis sp. nov. is a small dasyatid (males mature at 22 cm disc width), but it is the only Hemitrygon known to occur outside the western Pacific and eastern Indian Oceans. Hemitrygon yemenensis sp. nov. most closely resembles H. bennetti, but H. yemenensis is separable based on several characters including a longer and more narrowly pointed snout, shorter tail, and a longer disc and head. Hemitrygon yemenensis is unknown to science beyond the two type specimens collected nearly 120 years ago.